Long-term clinical course of a patient with mucopolysaccharidosis type IIIB - Ja Hye Kim; Yang Hyun Chi; Gu-Hwan Kim; Han-Wook Yoo; Jun Hwa Lee (Korean Pediatric Society, 2016)
Mucopolysaccharidosis type III (MPS III) is a rare genetic disorder caused by lysosomal storage of heparan sulfate. MPS IIIB results from a deficiency in the enzyme alpha-N-acetyl-D-glucosaminidase (NAGLU). Affected patients begin showing behavioral changes, progressive profound mental retardation, and severe disability from the age of 2 to 6 years. We report a patient with MPS IIIB with a long-term follow-up duration. He showed normal development until 3 years. Subsequently, he presented behavioral changes, sleep disturbance, and progressive motor dysfunction. He had been hospitalized owing to recurrent pneumonia and epilepsy with severe cognitive dysfunction. The patient had compound heterozygous c.1444C>T (p.R482W) and c.1675G>T (p.D559Y) variants of NAGLU. Considering that individuals with MPS IIIB have less prominent facial features and skeletal changes, evaluation of long-term clinical course is important for diagnosis. Although no effective therapies for MPS IIIB have been developed yet, early and accurate diagnosis can provide important information for family planning in families at risk of the disorder.